Diversity of AM Fungi and Their Exploitation for Disease Management in Horticultural Crops in NW Himalayan Region - Bharat, Narender K. (International Journal of Economic Plants, 2016)
Mycorrhiza, symbiotic association between fungi and roots of plants, supplies its plant partner with mineral nutrients and protects against soil-borne pathogens, whereas plant feeds fungus partner with photosynthates. Amongst mycorrhizae, arbuscular-mycorrhizae (AM) are common form occurring in association with most of plant species of different ecological regions. These fungi have been reported in thousand genera of plants including crops, shrubs and trees. 80 to 90 % of plants ranging from bryophytes to flowering plants have dynamic association of AM fungi. Apple, most important horticultural crop of north-western Himalayan region, is mycorrhizal dependent. In the region, AM fungi related to four genera viz., Glomus, Acaulospora, Gigaspora and Scutellospora were isolated. Frequency of occurrence was maximum (80%) in Glomus spp. followed by Acaulorpora spp. and Gigarpora spp. i.e. 10 and 9 % while minimum frequency of occurrence was in case of Scutellospora sp(1%). In Glomus, different species observed were identified to be G. fasciculatum, G. mosseae, G. macrocarpum, G. heterosporum, G. epigaeum and G. clarum amongst these maximum frequency of occurance was that of G. fasciculatum followed by G. mosseae and G. macrocarpum. Apple is affected by various soil borne diseases like root rot and replant disease. Recent reports have indicated that host plant inoculated with indigenous AM fungi increased tolerance to a wide range of root diseases in apple. Infection with mycorrhizal fungi elicited a resistance mechanism in inoculated plant which suppressed subsequent infection by fungal pathogens. Inoculation of apple root stock with a potent AM fungal isolate increased growth in apple replant disease (ARD) soil. Growth of apple root stock in ARD soil was more when AM fungi were inoculated along with antagonists like, Trichoderma spp. These indigenous AM fungi have potential of improving plant growth and suppressing soil borne pathogens in most of horticultural crops particularly apple.